Potent antidiuretic agonists, deamino-vasopressin and desmopressin, and their inverso analogs: NMR structure and interactions with micellar and liposomic models of cell membrane - Lubecka, Emilia A; Sikorska, Emilia; Sobolewski, Dariusz; Prahl, Adam; Slaninová, Jiřina; Ciarkowski, Jerzy (Biopolymers, 2016)
Deamination of vasopressin (AVP) enhances its antidiuretic activity. Moreover, introduction of D-Arg8 instead of its L enantiomer in deamino-vasopressin (dAVP) results in an extremely potent and selective antidiuretic agonist - desmopressin (dDAVP). In this study we describe the synthesis, pharmacological properties and structures of these two potent antidiuretic agonists, and their inverso analogs. The structures of the peptides are studied in micellar and liposomic models of cell membrane using CD spectroscopy. Additionally, three-dimensional structures in mixed anionic-zwitterionic micelles are obtained using NMR spectroscopy supported by molecular dynamics simulations. Our conformational studies have shown that desmopressin in a membrane mimicking environment adopts one of the characteristic for vasopressin-like peptides β-turn - in position 3,4. Furthermore, dDAVP shows the tendency to create a β-turn in the Cys6-Gly9 C-tail, considered to be important for the antidiuretic activity, and also some tendency to adopt a 5,6 β-turn. In desmopressin, in contrast to the native vasopressin, deamino-vasopressin and [D-Arg8]-vasopressin (DAVP), the Arg8 side chain, crucial for the pressor and antidiuretic activities, is very well exposed for interaction with the receptor, whereas Gly9, crucial for the pressor and uterotonic activities, is situated together with the C-terminal amide group very close to the tocin ring. The arrangements of the Gln4 and Asn5 side chains, being crucial for OT activity, also differ in desmopressin as compared to those of AVP, dAVP and DAVP. These differences in arrangement of the important for activities side chains are likely to explain extremely potent and selective antidiuretic activities of desmopressin. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 245-259, 2016.
Keywords: vodíková vazba; micely; desmopresin; uterus; fluoreny; antidiuretika; 1,2-dipalmitoylfosfatidylcholin; Protein Structure, Secondary; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; fosfatidylglyceroly; Female; Liposomes; techniky syntézy na pevné fázi; Cyclization; Micelles; sekundární struktura proteinů; zvířata; Phosphatidylglycerols; Solid-Phase Synthesis Techniques; potkani Wistar; Uterus; Oxytocics; simulace molekulární dynamiky; ženské pohlaví; Rats, Wistar; Molecular Dynamics Simulation; uterotonika; Fluorenes; liposomy; Hydrogen Bonding; Animals; Antidiuretic Agents; cyklizace; Deamino Arginine Vasopressin; 1,2-Dipalmitoylphosphatidylcholine